Polycyclic aromatic hydrocarbons volatilized from two polluted lagoons on Red Sea east coast: levels, sources, meteorological effects, and gas–particle partitioning. Issue 1 (3rd April 2021) - El-Maradny, A.; Rasiq, K. T.; Turki, A.; Shaban, Y. A.; Ghandourah, M.; Orif, M.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) in contaminated waterbodies can cause serious pollution to the adjacent atmosphere through volatilization. Gas–particle partitioning of PAHs controls the atmospheric concentrations of these pollutants. PAH levels in gaseous and particulate air samples were investigated near two polluted lagoons along the eastern coast of the Red Sea. Gas chromatography–mass spectrometry was used to analyze nine priority parent PAHs and nine methylated PAHs. Total gaseous and particulate PAHs ranged from 12.2 to 397.5 ng m −3, with an average of 125.6 ± 117.3 ng m −3, which was nearly 10-fold higher than that found in a previous study. Particulate PAHs (ranging from 0.04 to 16.32 ng m −3, with an average of 2.56 ± 1.71 ng m −3 ) contributed to less than 20% of the total atmospheric PAHs. Applied diagnostic indices showed that gasoline emissions were the main sources of PAHs in the lagoons' atmosphere. Multiparameter statistical analyses indicated that wind speed strongly affected the distribution of atmospheric PAHs. The average PAH gas–particle partitioning coefficient was 0.49 m 3 µg −1 (ranging from 2.1 × 10 −8 to 51.23 m 3 µg −1 ) and was significantly correlated with supercooled liquid vapor pressure. In addition to the effects of meteorological parameters and vehicle exhausts in the study area, the discharge of wastewater in the lagoons elevated PAH levels in the surrounding atmosphere.